Determination of Job Satisfaction and its Implications for the Organizational Commitment of the Management of the Indonesian Equestrian Sports Association (PORDASI) - Maswarni, Maswarni (Universitas Dharma Wacana, 2023)
The purpose of this study was to determine and analyze the influence of organizational culture, service leadership and appreciation partially or simultaneously on work. To find out the influence of organizational culture, Serving leadership and rewards and job satisfaction partially or simultaneously on Organizational Commitment. The population of this study were the administrators of the Indonesian Equestrian Sports Association (PORDASI) from 21 active provinces. The research method used in this study is a descriptive survey method and an explanatory survey with a sample size of 200 respondents, and the data analysis method used is SEM (Structural Equation Modeling). Based on research from structure 1, it proves that organizational culture, service leadership and rewards partially or simultaneously have a positive and significant effect on work with a contribution of 34.9% where organizational culture is the most dominant in influencing activities reflected in the dimensions of strengthening organizational culture by making routine events. Research from the results of construction 2 proves that organizational culture, service leadership, rewards and job satisfaction partially or simultaneously have a positive and significant effect on Organizational Commitment with a contribution of 80.8%. heart (humility). Another important finding from this research is the variable that acts as a partial mediation. Because only organizational culture and rewards are mediated by job satisfaction in influencing organizational commitment.. 9% where organizational culture is the most dominant in influencing activities reflected in the dimensions of strengthening organizational culture by making routine events. Research from the results of construction 2 proves that organizational culture, service leadership, rewards and job satisfaction partially or simultaneously have a positive and significant effect on Organizational Commitment with a contribution of 80.8%. heart (humility). Another important finding from this research is the variable that acts as a partial mediation. Because only organizational culture and rewards are mediated by job satisfaction in influencing organizational commitment.. 9% where organizational culture is the most dominant in influencing activities reflected in the dimensions of strengthening organizational culture by making routine events. Research from the results of construction 2 proves that organizational culture, service leadership, rewards and job satisfaction partially or simultaneously have a positive and significant effect on Organizational Commitment with a contribution of 80.8%. heart (humility). Another important finding from this research is the variable that acts as a partial mediation. Because only organizational culture and rewards are mediated by job satisfaction in influencing organizational commitment.. Research from the results of construction 2 proves that organizational culture, service leadership, rewards and job satisfaction partially or simultaneously have a positive and significant effect on Organizational Commitment with a contribution of 80.8%. heart (humility). Another important finding from this research is the variable that acts as a partial mediation. Because only organizational culture and rewards are mediated by job satisfaction in influencing organizational commitment.. Research from the results of construction 2 proves that organizational culture, service leadership, rewards and job satisfaction partially or simultaneously have a positive and significant effect on Organizational Commitment with a contribution of 80.8%. heart (humility). Another important finding from this research is the variable that acts as a partial mediation. Because only organizational culture and rewards are mediated by job satisfaction in influencing organizational commitment.